GERMPLASM EVALUATION OF PEARL MILLET [Pennisetum glaucum (L.) R. Br.] FOR DOWNY MILDEW INFECTION, AGRONOMIC TRAITS AND YIELD - Ati, Maryam; Ikpe, Jude (FUDMA Journal of Sciences, 2020)
Pearl millet [Pennisetum glaucum (L.) R. Br.] is the most suitable crop for arid and semiarid conditions because of its drought resistance compared to sorghum and maize. Farmers prefer the crop as low cost, low risk option not only by choice but also by necessity. The aim of the study was to characterize the millet varieties according to their performance, score for downy mildew and select those that are resistant to the infections, select for earliness and select varieties with the highest yield. The experiment was carried out in the Research Farm of the Department of Crop Production and Protection, Federal University Dutsin-Ma. Seventy-two new varieties of pearl millet collected from Niger Republic were sown during the rainy season. Randomized Complete Block Design was used for the field evaluation. The result from the research indicated that out of the seventy-two pearl millet varieties, forty-eight varieties were highly resistant (HR) to downy mildew, nine varieties were resistant (R) to downy mildew, twelve varieties were moderately resistant (MR) to downy mildew, while three varieties were moderately susceptible (MS) to downy mildew. Two varieties were extra early in maturity (65 days), three varieties were early maturing (70 days), and twenty-five varieties were mid-maturing (75 days), while forty-two varieties were late maturing (83 days). Seven varieties have low yield and did not perform well in the environment. Sixty-four varieties had average yield and variety (ISP 3974) had the highest yield. Therefore, they are recommended for advanced trials and subsequence breeding programmes.